Influência da adubação nitrogenada e de etil-trinexapac no crescimento e produtividade do trigo - Motter, Leandro (2007)
The wheat that's a culture of high risk, due environmental conditions and weather, and another factors like pests, diseases and fallen plant index. This latter is responsible for losses considerable of grains, since that difficulty a good deal the harvest, occur loss of yield. Thus, the present work if considers to evaluate the effect of the vegetal retardant trinexapac-ethyl, on reduction of the postage of the wheat CD 104, in an attempt to minimize problems caused at fallen plant index related on the manure spreading nitrogen on cover, as well as access the growth and productivity in response the nitrogen and on the application of vegetal retardants. The experiment was developed Experimental Station from COPACOL in the city of Cafelândia - PR. The experimental design was he of blocks at random, in factorial outline (2X6X6), being two levels of nitrogen on cover (40 and 80 kg ha-1) treatments gotten for the combination of six levels of the vegetal retardant 0.0; 0.2; 0.4; 0.6; 0.8; and 1.0 L ha-1) and six collection of plants [20, 35, 50, 65, 80 and 95 days after the emergence (DAE)], with four repetitions. During the conduct after 20 DAE, plans were collected for each 14 days about to ends of biometric analysis and growth. Each one was realized in a randomized way taking plants in 0,30 m in the tillage line, inside from parcel useful in each experimental parcel. In the harvest the components of the yield had been evaluated, productivity and fallen plant index. Trinexapac-ethyl reduces the height of plants and no influence the productivity of the wheat CD 104, but it showed - if effective into the control of fallen plant index, reducing possible losses on harvest. The levels of N applied on cover presented values positive into the increase from productivity of the wheat, by highlighting - if the use of 80 kg ha-1